Building a Culture of Retirement: Class, Politics and Pensions in Post-World War II Ontario - Struthers, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 1997)
AbstractThis paper examines four factors which influenced the development of old age pensions in Canada after World War II. The legacy of Canada's original means-tested pension program, the class politics of pension bargaining between business and organized labour on both sides of the border, the policy example of Social Security in the United States, and the key importance of the insurance and investment industry lobby operating through successive Conservative governments in Ontario, are highlighted as critical factors which affected the timing and limited the scope of Canada's public pension system. The residualist design of Old Age Security in 1951 and Ontario's success in gaining a veto over reforms to the Canada Pension Plan in 1965 are singled out as a key factors behind the current vulnerability of Canadian public pensions to fiscal cutbacks compared to the Social Security in the United States.